2013
DOI: 10.4081/pmc.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and duration of breastfeeding during the first six months of life: factors affecting an early cessation

Abstract: RiassuntoOBIETTIVI: valutare durata media e prevalenza dell'allattamento al seno nei primi sei mesi di vita in neonati sani nati a termine e individuare le possibili cause responsabili della precoce sospensione. METODI: studio osservazionale, prospettico. Sono state arruolate 100 donne non fumatrici, di razza caucasica, intenzionate ad allattare per almeno 12 settimane. La raccolta dati è avvenuta tramite 3 questionari (somministrati all'arruolamento, 7 giorni, 1, 2, 3 e 6 mesi), volti a indagare parametri ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
7
1
1
Order By: Relevance
“…Our results consistent to another local study (2014) which showed 65.8% of Iranian mothers had breastfeeding in 4 first months but this rate decreased to 24 months [2]. Spears and Garbarino in their studies also revealed that the prevalence rate of the breastfeeding initiation rate was much more than breast feeding sustaining after 6 months or latter [17] [18].…”
Section: Discussionsupporting
confidence: 92%
“…Our results consistent to another local study (2014) which showed 65.8% of Iranian mothers had breastfeeding in 4 first months but this rate decreased to 24 months [2]. Spears and Garbarino in their studies also revealed that the prevalence rate of the breastfeeding initiation rate was much more than breast feeding sustaining after 6 months or latter [17] [18].…”
Section: Discussionsupporting
confidence: 92%
“…Among the main difficulties encountered during breastfeeding, engorged breasts, nipple fissures, painful breasts [18,19], difficulty in latching, drying milk and rejection of the baby [19] are the most frequently reported by mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Women's lack of knowledge about how to prevent or solve common problems at the start of breastfeeding and the unavailability of professionals in the UBS, who have an expanded vision that goes beyond clinical management and supports mothers [22], may be causes of breastfeed failure ,since a process of maternal suffering based on engorgement, fissures and the perception of hunger through the behavior of the newborn begins, which contributes to the early interruption of breastfeeding [18,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, of those mothers who do choose to initiate breastfeeding, many encounter problems which can lead to early cessation. Such factors include the perception that their milk supply is inadequate (e.g., [ 7 ]), and concern over the infant’s nutrition and lack of weight gain [ 8 ]. Physical pain can also lead to early cessation (e.g., [ 8 ]) as can emotional distress, such as depression or stress, and resultant feelings that breastfeeding is interfering with bonding.…”
Section: Introductionmentioning
confidence: 99%